The Role of the Transnational NGO Oxfam in Poverty Alleviation in Indonesia - Bernicha Eka (Universitas Negeri Yogyakarta, 2026)
Poverty remains one of the development challenges facing Indonesia today. Poverty is not only related to low income levels but also includes limited access to education, health services, employment, and other economic resources. To address these issues, the government cannot work alone but requires support from various non-state actors, including transnational non-governmental organizations (NGOs). This study aims to analyze Oxfam's role in poverty alleviation in Indonesia. This study uses a qualitative method with a descriptive approach through a literature review sourced from books, scientific journals, official reports, and relevant documents. The results show that Oxfam contributes to poverty alleviation through community economic empowerment programs, strengthening food security, empowering women, humanitarian assistance, and policy advocacy. One form of this contribution is seen through programs to empower women and strengthen community livelihoods in vulnerable areas, such as East Nusa Tenggara and Central Sulawesi, which aim to increase economic independence and community resilience to various social and economic risks. In addition, Oxfam also supports post-disaster community recovery by providing humanitarian assistance and strengthening local community capacity. Although program implementation still faces various challenges, such as limited funding, coordination between stakeholders, and program sustainability, Oxfam continues to make significant contributions to poverty alleviation efforts and to realizing inclusive and sustainable development in Indonesia.